The Effect of Using The Integration Of ICT and Realia Media on Students’ Writing Descriptive Text Ability - Nurbaidah, Nina; Inul, Silvana; Puspita, Puspita; Sahrul, Sahrul; Nasari, Ummi (International Journal of English and Applied Linguistics (IJEAL), 2026)
The purposes of this research to know the extent of using realia media on students’ writing descriptive text at the eighth grade of SMP Negeri 8 Padangsidimpuan, To know the extent of the students’ writing descriptive text before and after using realia media at the eighth grade of SMP Negeri 8, to find out whether there is any significant effect of students’ writing descriptive text after using realia media at the eighth grade of SMP Negeri 8 Padangsidimpuan.The method used in this research was quantitative method. The population of this research the eighth grade students consists 154 students. The researcher uses purposive sampling technique to get the sample that VIII-1 consists 30 students. The data was obtained by distributing the observation sheet and test. It is found that the result of the used of Realia Media in teaching writing descriptive text at the eighth grade of SMP Negeri 8 Padangsidimpuan in 2024/2025 academic year is 80%, it is categorized “very good”. The score of  students writing descriptive text before using realia media was 58 it is categorized “fair to poor”. While, the students writing descriptive text after using realia media was 76,7 category “good” category. There is significant effect of students’ writing descriptive text after using realia media at the eighth grade of SMP Negeri 8 Padangsidimpuan in 2024/2025 academic year that significant was less that 0,05 (0,00<0,05) and Alternative Hypothesis is accepted.